Conceptual evolution of facilitating taking account the challenges of complexity - Arce R., Rodrigo (2017)
Currently there is no definition of facilitation to unify its various practices and expressions. Although this reality realizes the great creative wealth of practical facilitation affects the theoretical and methodological dispersion is diluted among the various forms of social intervention. This article reviews the various definitions widely found in the literature on facilitation and proposes an inclusive definition. This definition states that the provision relates to processes and functions that allow you to interact with the paradigms, thoughts, feelings, emotions and events (speeches, attitudes and practices) of individuals and groups in a systemic and contextual framework so that it can address the complexity through the deployment of all its capacities, abilities and potential oriented to achieve dynamic equilibrium to establish relationships, links, understandings or agreements that eventually may become targets deriving a transformative actions in accordance with nature and the cosmos. It is recommended that the proposed definition can be tested and put into consistency regarding the different forms of the field of facilitation.